2018
DOI: 10.1140/epjqt/s40507-018-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanobob: a CubeSat mission concept for quantum communication experiments in an uplink configuration

Abstract: We present a ground-to-space quantum key distribution (QKD) mission concept and the accompanying feasibility study for the development of the associated low earth orbit nanosatellite payload. The quantum information is carried by single photons with the binary codes represented by polarization states of the photons. Distribution of entangled photons between the ground and the satellite can be used to certify the quantum nature of the link: a guarantee that no eavesdropping can take place. By placing the entang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…Many recent proposals foresee the use of nano-satellites (e.g. CubeSats [58][59][60]) for QKD implementation [9,[61][62][63][64]. The possibility to deploy many of such satellites in a single mission, to share the vector with other payloads and the modular nature lowers considerably the launch and building cost of these devices.…”
Section: Cube-sat Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent proposals foresee the use of nano-satellites (e.g. CubeSats [58][59][60]) for QKD implementation [9,[61][62][63][64]. The possibility to deploy many of such satellites in a single mission, to share the vector with other payloads and the modular nature lowers considerably the launch and building cost of these devices.…”
Section: Cube-sat Performance Analysismentioning
confidence: 99%
“…The possibility to deploy many of such satellites in a single mission, to share the vector with other payloads and the modular nature lowers considerably the launch and building cost of these devices. They are usually loaded with smaller optics, of diameter 10 cm, even if larger apertures can be achieved with the use of deployable optics or bigger CubeSats (like the 12-Units satellite proposed in [63]). When used as transmitter, in the down-link configuration, the smaller aperture creates beams with much higher intrinsic divergence than the case studied in section 3.…”
Section: Cube-sat Performance Analysismentioning
confidence: 99%
“…Interesting research is ongoing on the use of quantum cryptography. Some missions have been designed and developed, using nanosatellites and CubeSats, which show the feasibility of ground-to-space quantum key distribution (QKD) [75][76][77][78]. QKD uses individual light quanta in quantum superposition states to guarantee unconditional communication security between distant parties.…”
Section: Perspectives and Open Challengesmentioning
confidence: 99%
“…a combination of a 50:50 beam splitter (BS), two PBSs, a HWP and four detectors, such as proposed for the 12U CubeSat of Ref. [16]) or an extremely fast active one (e.g. rapid Pockels cells).…”
Section: Basis Choice and Polarization Analysismentioning
confidence: 99%
“…Previous studies such as Refs. [12][13][14][15][16] have shown that space-based Q.Com is in principle feasible (also with small satellites) and culminated in two successful Q.Com satellites as well as other quantum experiments in space [17]. Recent efforts have evaluated the feasibility of downlinks [18] while others have attempted to solve the technological challenges identified by space-certifying detectors and sources of entanglement [19].…”
Section: Introductionmentioning
confidence: 99%